Interfacial water at hydrophobic and hydrophilic surfaces: depletion versus adsorption - Janecek, Jirí; Netz, Roland R (Langmuir, 2007)
The structure of the water-solid interface for widely varying surface properties is investigated with Monte Carlo simulations using the SPC/E water model. Of particular interest is the relation between the wetting coefficient as a measure of the hydrophobicity of the substrate and the density depletion close to the solid surface. The substrates are modeled as rigid ordered lattices of sites that interact with water molecules through an orientation-independent Lennard-Jones potential of varying strength. Hydrophilic character is obtained by addition of polar hydroxyl groups on the substrate surface, and the influence of density, spatial distribution, and angular orientation of the polar groups on the interfacial water structure is studied.
Keywords: Wettability; voda; chemické modely; Models, Chemical; Water; smáčivost; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions